Roles of core nosZ denitrifiers in enhancing denitrification activity under long-term rice straw retention - Zhang, Shijie; Hou, Mengyao; Li, Bing; Guan, Panfeng; Chi, Qing; Sun, Hao; Xu, Hangbo; Cui, Dongjie; Zhu, Yupan (Frontiers in Plant Science, 2025)
The denitrification process is known to contribute to soil nitrogen (N) loss, which is strongly affected by fertilization strategies; however, the effects of distinct straw retention modes on soil denitrification activity have rarely been discriminated and the underlying mechanisms remain unclear. This study coupled field and incubation experiments to explore the characteristics of soil denitrification activity, soil and standing water physicochemical properties, and the abundance, community diversity, and co-occurrence network of nosZ denitrifiers, based on a paddy field implementing 10-year straw retention under a rice–wheat rotation system. Four straw retention treatments with equivalent chemical fertilizers were applied, namely no straw (NS), wheat straw only (WS), rice straw only (RS), and wheat and rice straw (WRS). Results indicated a significant increase (by 41.93–45.80% when compared to that with NS) in the soil denitrification activity with RS and WRS. Correspondingly, treatments with rice straw retention resulted in the development of a similar community composition (P < 0.05), structure (P = 0.001), and more positively interconnected network, as well as similar specific keystone taxa of nosZ denitrifiers, relative to those in non-rice straw mode. Under long-term rice straw retention conditions, the core nosZ-denitrifying phylogroups shifted (r = 0.83, P < 0.001), with the recruitment of keystone taxa from the phyla Bacteroidetes and Euryarchaeota playing a key role in enhancing denitrification activity and stimulating N loss. Accordingly, in a rice–wheat rotation field, the practice of wheat straw retention in a single season is recommended because it will not markedly sacrifice soil N availability impaired by the denitrification process.